Dating of detrital zircon grains and fossils from Late Palaeozoic sediments of the Baruo area, Tibet: constraints on the Late Palaeozoic evolution of the Lhasa terrane. Issue 4 (3rd March 2020) - Wang, Ming; Zeng, Xiao-wen; Xie, Chao-Ming; Danzeng, Awang; Li, Cai; Fan, Jian-Jun; Li, Hang
ABSTRACT: To determine the Late Palaeozoic evolution of the Lhasa terrane, we report the results of field mapping, petrological and fossil investigations, and U–Pb dating of detrital zircon grains (n = 474) from lower-greenschist-facies clastic rocks of the Lagar Formation in the Baruo area, Tibet. Our results indicate that the Lagar Formation was deposited during the Late Carboniferous to Early Permian in a shallow-marine environment on the northern margin of Gondwana. Glacial marine diamictites are common within the Lagar Formation and record glaciation of Gondwana during the Late Palaeozoic. Moreover, the detrital materials of the Lagar formation originated mostly from the collision orogenic belt. The ages of detrital zircon grains from the Lagar Formation make up five main groups with ages of 410–540 Ma, 550–650 Ma, 800–1100 Ma, 1600–1800 Ma, and 2300–2500 Ma, which display three characteristic age peaks at 1150, 2390 and 2648 Ma. We tentatively suggest that the Lhasa terrane was a shallow-marine basin under the influence of the Gondwanan glaciation during the Late Carboniferous–Early Permian. Graphic abstract: